Effective Adsorption of Colorants from Sugarcane Juice by Bagasse-Based Biochar-Hydroxyapatite Composite - Cheng Wang; Mengying Luo; Caifeng Xie; Kai Li; Fangxue Hang; Changrong Shi; William O. S. Doherty (Foods, 2022)
The clarification of sugarcane juice is a crucial stage in the sugar manufacturing process, as it affects evaporator performance, sugar quality and yield. The emergence of environmentally friendly and efficient adsorption technology has resulted in widespread interest in carbon-based materials. However, their low adsorption capacity and reusability make them unsuitable for processing sugarcane juice. Here, we provide a cost-effective and sustainable method to dope hydroxyapatite (HAP) nanoparticles on porous carbon (BBC) derived from sugarcane bagasse (BBC-HAP). The composite shows excellent adsorption capacity for color extract from sugarcane juice of 313.33 mg/g, far more effective than the commercially available carbon-based adsorbents. Isotherm studies show that the adsorption of BBC-HAP composite to the colorants is a monolayer process. The pseudo-first-order (PFO) and pseudo-second-order (PSO) kinetic models demonstrate that the adsorption process is dominated by chemisorption and supplemented by physical adsorption.